Answers

2016-06-21T22:33:29+08:00
Thus       [(a+7)+(a+3)]/2   =  3a + 9 
               (2a + 10)/2   =  3a + 9
                  a + 5   =   3a + 9
                   2a = - 4
                     a   =    -2
0
san po ilagay Ang /2 ?
under po ng (a+3) ?
the arithmetic mean of x and y = ( x+y)/2 let say x = 2 and y = 8, arithmetic mean = (2+8)/2 = 10/2 = 5 in your case x = a+7 & y = a+3 and AM = 3a + 9
paano naging 2a=-4!!!!????
transfer a to the right of the equation it become - a so 3a-a =2a and transfer 9 to the left it become -9 so 5 -9 = -4 hope you are able to understand